Analysis of Precipitable Water Vapour in Nigeria using GNSS Observations - Bala, Ipalibo Ateriye (2022)
Water Vapour estimation using ground-based Global Navigation Satellite System (GNSS) observations is a well-established technology that contributes to weather forecast, research, and climate monitoring. Water vapour in the atmosphere is directly related with precipitation that may lead to extreme event (e.g., floods). The application of GNSS to sense the total amount of water vapour integrated along the signal path in the troposphere is what is referred to as GNSS meteorology. GNSS has the advantage of all-weather condition, low cost with high temporal and spatial resolution when compared to other classical methods of water vapour measuring that are expensive and/or with low spatial and temporal coverage. When GNSS signals are transmitted from GNSS satellites in space to ground-based GNSS receivers, they experience a tropospheric delay (an error source in GNSS positioning) often represented in GNSS meteorology as the Zenith Total Delay (ZTD). The ZTD is the sum of the Zenith Hydrostatic Delay and the Zenith Wet Delay and it is one of the products of GNSS data processing. The ZTD can be converted to Precipitable Water Vapour (PWV) when surface temperature and pressure values are known at the GNSS site using a conversion factor (?) that is dependent on the weighted mean temperature (Tm) and pressure. This dissertation focuses on the estimation and analysis of water vapour in Nigeria using GNSS observations. The Nigerian Permanent GNSS Network (NIGNET) stations observations and products were retrieved from the infrastructure implemented by Office of the Surveyor General of the Federation (OSGoF). Processing of the data was carried out using online software (GipsyX) for the estimation of ZTD. Fifteen GNSS stations were used in this research and the period 2009 to 2021 was considered. The characteristics of the ZTD over the territory of Nigeria was investigated. The range of ZTD variation in Nigeria for the period used in this research was found to be approximately between 1900mm to 2700mm in the NIGNET stations. The two main seasons in Nigeria were significantly noticed as low peaks were found to be occurring during the dry (winter) season while high peaks were remarkably seen during the rainy (summer) season. The amplitude of the seasonal variation within the period under investigation is between a minimum of 36mm to a maximum of 124mm with the Northern region having higher values than the Southern part. It was discovered ultimately by the results obtained from the analyses, that ZTD variation in both the Northern and Southern regions are influenced by the 4 distinct climates and other local weather conditions including temperature and the trade wind from Sahara Desert and the Atlantic Ocean.